2005
DOI: 10.1002/adsc.200505086
|View full text |Cite
|
Sign up to set email alerts
|

Design of Ionic Phosphites for Catalytic Hydrocyanation Reaction of 3‐Pentenenitrile in Ionic Liquids

Abstract: Abstract:The synthesis and characterization of a novel class of ionic phosphites bearing either a single cationic group obtained by quaternization of aminophosphites or three cationic groups prepared by reaction of phosphorus trichloride with imidazolium phenols are reported. The catalytic hydrocyanation reaction of 3-pentenenitrile (3PN) into adiponitrile has been performed in the presence of Ni(0) with ionic phosphite ligands, and a Lewis acid in biphasic ionic liquid/organic solvent system. The screening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Unlike the traditional synthetic approach to ionic phosphites through quaternization of P,N-bidentate compounds, [6] the novel phosphites and diamidophosphites L1-L3 were synthesized by a direct phosphorylation of an appropriate ionic liquid in CH 2 Cl 2 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike the traditional synthetic approach to ionic phosphites through quaternization of P,N-bidentate compounds, [6] the novel phosphites and diamidophosphites L1-L3 were synthesized by a direct phosphorylation of an appropriate ionic liquid in CH 2 Cl 2 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…[14] Table 3 and Table 4 show that activity (and enantioselectivity) depend upon the nature of the ligand, a conclusion noted earlier in other systems. [6] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After optimizing the reaction conditions, we found that sodium alcoholate generated from optically pure (+)-(P,S)-18 reacted smoothly with commercially available chlorophosphites 19 and 20 or chlorophosphites 21 [30] and 22, [31] whose syntheses have been described in the literature. The formation of phosphites could be easily monitored by 31 P{ 1 H} NMR spectroscopy, as the conversion of chlorophosphites into phosphites was indicated by a significant shift in the signal of the phosphorus atom (for the chemical shifts of phosphorus atoms in chlorophosphites 19-22 and phosphites 23-26, see the Supporting Information).…”
Section: Synthesis Of Helical Phosphitesmentioning
confidence: 99%